2005
DOI: 10.1029/2004gl021669
|View full text |Cite
|
Sign up to set email alerts
|

Two components of ionospheric plasma structuring at midlatitudes observed during the large magnetic storm of October 30, 2003

Abstract: We consider VHF amplitude scintillations, GPS phase fluctuations, ionosonde measurements, maps of GPS total electron content (TEC), observations of daytime aurora and TIMED GUVI images during the large magnetic storms of October 29–31, 2003, and find two distinct classes of plasma processes that produce midlatitude ionospheric irregularities. One is associated with auroral plasma processes; the other, with storm enhanced density (SED) gradients, a part of which occur in close proximity to sub‐auroral polarizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 48 publications
(52 citation statements)
references
References 11 publications
2
50
0
Order By: Relevance
“…With an approximate spacecraft velocity of 7 km/s, a spacecraft will take approximately 10 seconds to traverse the SED plume; therefore a measurement cadence of at least 0.5 seconds was required of DICE to define the plume and the related (broader) plasma electric field structures. Ionospheric irregularities are of great interest for space weather and it has been shown that small scale irregularities form on the edges of large SED gradients (Foster 1993;Basu et al 2003). The physical instability mechanism is not known, so directly measuring small scale electric fields in association with larger scale SEDs is quite valuable.…”
Section: Science Researchmentioning
confidence: 99%
“…With an approximate spacecraft velocity of 7 km/s, a spacecraft will take approximately 10 seconds to traverse the SED plume; therefore a measurement cadence of at least 0.5 seconds was required of DICE to define the plume and the related (broader) plasma electric field structures. Ionospheric irregularities are of great interest for space weather and it has been shown that small scale irregularities form on the edges of large SED gradients (Foster 1993;Basu et al 2003). The physical instability mechanism is not known, so directly measuring small scale electric fields in association with larger scale SEDs is quite valuable.…”
Section: Science Researchmentioning
confidence: 99%
“…The SYM-H attains its maximum negative value of À432 nT at 2256 UT. Basu et al [2001bBasu et al [ , 2005b have shown that when a sudden intensification of the ring current occurs leading to SYM-H decreases at such a large rate, the electric field penetration from high latitudes causes the formation of ionospheric irregularities of electron density in the midlatitude and the equatorial region. The two arrows in the bottom panel, one during the rapid decrease and the other near the minimum SYM-H, specify the times of the equator crossing of two successive orbits of the DMSP F14 satellite that detected equatorial plasma bubbles and deep plasma bite-outs, as will be shown in subsequent diagrams.…”
Section: Storm Of 30 -31 October 2003mentioning
confidence: 99%
“…Modeling the disturbance dynamo phase is complicated because the disturbance dynamo electric fields have to operate on an ionosphere that has been modified by the initial prompt penetration electric fields [Maruyama et al, 2005]. Our understanding of this complex interaction can be advanced by global ionospheric modeling of many storms and model validation with observations at globally dispersed locations [Fejer et al, 1990;Greenspan et al, 1991;Fejer and Scherliess, 1995;Fejer and Emmert, 2003;Basu et al, 2001aBasu et al, , 2001bBasu et al, , 2005aBasu et al, , 2005bMartinis et al, 2005].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, GPS TEC measurements have detected the passage of atmospheric gravity waves (AGW) at mid and high latitudes (Ho et al, 1998a;Saito et al, 1998;Shiokawa et al, 2002), improved understanding of the dynamics of the magnetically-disturbed mid-latitude ionosphere (Basu et al, 2005), and helped the forecast of the onset of equatorial plasma irregularities (Valladares et al, 2001). The first studies of AWG using GPS receivers employed 150+ globally distributed receivers to indicate the existence of small TEC enhancements developing simultaneously at both north and south auroral regions (Ho et al 1998a, b).…”
Section: Introductionmentioning
confidence: 99%